Vibration Analysis of Low Height-to-Span Ratio Pedestrian Bridge under Human-Induced Excitation - Wei Wang; Rui An; Huihui Huang; Jie Li; Jinghang Niu; Huan Liao; Jian Jiao; Zhiqiang Li; Yuekai Tao (Advances in Civil Engineering)
Driven by the aesthetic pursuit of the urban landscape, pedestrian bridges become longer, lighter, and slender, which may be susceptible to unacceptable vibrations induced by human activities. This paper presented on-site vibration tests of a pedestrian bridge with a very low height-to-span ratio (1/60). The vibration characteristics and dynamic responses were analyzed using environmental, heel-drop, and walking tests. Then, a verified finite model was established to investigate the effect of the height-to-span ratio and the concrete filling ranges of tree-like steel piers on the vibration characteristics and acceleration responses of this kind of pedestrian bridges. Moreover, the relationship between different peak accelerations under heel-drop and walking at various frequencies by the same person was detailed and studied experimentally and by computer simulation, after which the ratios of the peak acceleration during walking and the one under heel-drop were recommended. Finally, a method that demonstrates the feasibility of predicting the peak acceleration of pedestrian bridges of a small height-to-span ratio across a range of walking frequencies was proposed based on a simplified heel-drop load model developed according to 60 time-history records.